The collection Visser at the Kröller-Müller Museum. - Blotkamp, Carel; De Decker, Anny; van Straaten, Evert J.; van den Bosch, Paula (Otterlo : Stichting Kröller-Müller Museum, 2000)
Andre, Carl ; Armando ; Beuys, Joseph ; Broodthaers, Marcel ; Brouwn, Stanley ; Buren, Daniel ; Christo ; Darboven, Hanne ; Dekkers, Ad ; de Maria, Walter ; Dibbets, Jan ; van Eyck, Aldo ; Riverhead (New York) ; Fontana, Lucio ; Fulton, Hamish ; Gilbert & George ; Gilbert, Stephen ; van Golden, Daan ; Holzer, Jenny ; Judd, Donald ; Kelly, Ellsworth ; Kiefer, Anselm ; van Koningsbruggen, Rob ; Kosuth, Joseph ; LeWitt, Sol ; Long, Richard ; Lueg, Konrad ; Manzoni, Piero ; Marden, Brice ; Morris, Robert ; Nauman, Bruce ; Nordman, Maria ; Oldenburg, Claes ; Panamarenko ; Penck, A.R. ; Polke, Sigmar ; Raetz, Markus ; Rückriem, Ulrich ; Smithson, Robert ; Struycken, Peter ; Visser, Carel ; Weiner, Lawrence
2 ex.: catalogus: The collection Visser at the Kröller-Müller Museum, 413 p. : ill. + supplement, 95 p. : ill.
bibliog. p.411-412
Nederlands & Engels
The collection Visser at the Kröller-Müller Museum, Kröller-Müller Museum, Otterlo, 18.08 - 17.09.2000
boek